Minibus taxis in Kampala's paratransit system: Operations, economics and efficiency - Ndibatya, Innocent; Booysen, M.J. (Journal of Transport Geography, 2020)
Most cities in sub-Saharan Africa rely for their public transport on paratransit in the form of fourteen- to twenty-seater privately owned and mostly old minibus taxis. The system is often seen as disorganized, unregulated and inefficient. To assess the accuracy of this picture, we analyzed the operations and economics of Kampala's minibus taxi system and its efficiency from the passengers' and the drivers' perspectives, using ‘floating car data’. We found that the picture is largely accurate. Our findings suggest the need for moderate transformation: adequate enforcement of regulations, reorganization of ownership, renewal of fleets, and integration of ICT systems to facilitate scheduling, booking and fare collection. This will help to make the system safer, cleaner and more efficient for Kampalan commuters and more stable, secure and profitable for the minibus taxi drivers and the mini industries that depend on them.
Keywords: Minibus taxi; Paratransit; Public transport; Kampala; Africa